Immunologic Studies of Antithrombin III Heparin Cofactor in the Newborn - Hathaway, W E; Neumann, L L; Borden, C A; Jacobson, L J (Thrombosis and Haemostasis, 1978)
Serial quantitative immunoelectrophoretic (IE) measurements of antithrombin III heparin cofactor (AT III) were made in groups of well and sick newborn infants classified by gestational age. Collection methods (venous vs. capillary) did not influence the results; serum IE measurements were comparable to AT III activity by a clotting method. AT III is gestational age-dependent, increasing from 28.7% of normal adult values at 28-32 weeks to 50.9% at 37-40 weeks, and shows a gradual increase to term infant levels (57.4%) by 3-4 weeks of age. Infants with the respiratory distress syndrome (RDS) show lower levels of AT III in the 33-36 week group, 22% vs. 44% and in the 37-40 week group, 33.6% vs. 50.9%, than prematures without RDS. Infants of 28-32 week gestational age had only slight differences, RDS = 24%, non-RDS = 28.7%. The lowest levels of AT III were seen in patients with RDS complicated by disseminated intravascular coagulation and those with necrotizing enterocolitis. Crossed IE on representative infants displayed a consistent pattern which was identical to adult controls except for appropriate decreases in the amplitude of the peaks. The thrombotic complications seen in the sick preterm infant may be related to the low levels of AT III.